2019
DOI: 10.20452/pamw.14866
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of family history, genetic risk score and physical activity in distinguishing type 2 diabetes prevalence

Abstract: related to obesity and insulin resistance. The exact pathogenesis of T2D is still unclear; however, it is known that both environmental and genetic factors are involved. The rapid development of genome-wide association studies in the last decade has facilitated the identification of more than 100 susceptibility loci for T2D. 2 These discoveries resulted in dissemination of the genetic risk scores (GRSs), combining information from multiple single nucleotide polymorphisms (SNPs) into a summary measure of a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…These results underscore the importance of being physically active for T2D prevention, particularly in those with high genetic risk. Our finding is in line with two studies using 19 SNPs in Poland and 49 SNPs in nine European countries 25 26. In contrast, Klimentidis and his colleagues found that the protective effect of physical activity in those with higher genetic risk was weaker compared with those with lower genetic risk using a PRS comprised of 65 SNPs in the USA 27.…”
Section: Discussionsupporting
confidence: 91%
“…These results underscore the importance of being physically active for T2D prevention, particularly in those with high genetic risk. Our finding is in line with two studies using 19 SNPs in Poland and 49 SNPs in nine European countries 25 26. In contrast, Klimentidis and his colleagues found that the protective effect of physical activity in those with higher genetic risk was weaker compared with those with lower genetic risk using a PRS comprised of 65 SNPs in the USA 27.…”
Section: Discussionsupporting
confidence: 91%
“…The typical patient with T2DM is obese, male, aged 63 years, suffering from T2DM for 10 years [ 2 ], a smoker, treated with antihypertensives, statin and metformin, with a glycated hemoglobin (HbA1c) of 55 mmol/mol (7.2%) [ 3 ]. Additionally, worse glycemic control is seen in patients with a positive family history of T2DM [ 4 ]. The prevalence of cardiovascular disease (CVD) among patients with T2DM varies from 21 [ 5 ] to 32% [ 2 , 3 ], which is much higher than in the general population (10.6%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants and Study Design. A population-based sample from the 1000PLUS Cohort Study group was enrolled in this study, consisting of 1,549 Caucasian individuals of Polish origin (aged 18-79 y), recruited between 2007-2019 as described previously (20,39,40). For this analysis, we included subjects who did not have any endocrine, renal, hepatic and gastrointestinal disorders and were not taking any treatments (including dietary supplements, following any speci c eating pattern or diet etc.)…”
Section: Methodsmentioning
confidence: 99%